Modelling System Generation: Towards the New Model in Albania and SEE Countries - Karapici, Valbona; Matraku, Doriana (New Energy Exploitation and Application, 2024)
The electricity utility industry is undergoing rapid and irreversible changes resulting from volatile fuel costs, transmission access, less predictable load growth and a more complex regulatory environment. Due to the rising importance of renewable (and variable) energy sources, power systems are now more vulnerable to uncertainties and intermittent in supply. Hydropower plays an important role in the energy mix and power market, helping in providing base and peak load power as well as being the ‘fuel’ (water) not subject to fluctuations in the market; these paving the way toward a clean energy by 2030 and net-zero emissions by 2050 as part of de-carbonization agenda. All production and conversion processes in the energy sector require Water for nearly including fuel extraction and processing (fossil and nuclear fuels as well as biofuels) and electricity generation (thermoelectric, hydropower, and renewable technologies). This paper’s objective is to analyze cross-border trade in SEE through economic electricity exchange, while also exploring reasons for promoting Hydroelectricity. This is achieved through the following objectives: first, an overview is made of the available energy and economic data in the region; second, a model is developed for regional least cost expansion planning when allowing for cross-border trade. These aim to assess electricity supply and demand in the region with the purpose of making a comparative analysis regarding energy resource endowments.